Analisis Total Plate Count (TPC) Dan pH Pada Ikan Mujair (Oreochromis mossambicus) Dengan Perbedaan Suhu Dan Lama Penyimpanan - Rachmawati, Nandya Fitri; Sulthoniyah, Siti Tsaniyatul Miratis; Ulfa, Rosiana; Amalia, Djingga (Jambura Fish Processing Journal, 2024)
This research aims to determine the effect of quantitative differences in temperature and storage time on physical changes, TPC values and pH in fresh tilapia fish (Oreochromis mossambicus). The analytical method used is quantitative descriptive analysis. The results showed that the physical characteristics changed in terms of color, texture and aroma with temperature and storage time. The TPC value results were obtained at a temperature of 0 with a storage period of 0 hours, 24 hours, and 48 hours, namely 9.6 x 104 colonies /mL, 9.5 x 104 colonies /mL and 9.4 x 104 colonies/mL. The results of the TPC value were obtained at a temperature of 5  with a storage duration of 0 hours, 24 hours, and 48 hours, namely 9.8 x 104 colonies/mL, 9.7 x 104 colonies/mL and 9.6 x 104 colonies/mL. The TPC value results were obtained at a temperature of 27  with a storage period of 0 hours, 24 hours, and 48 hours, namely 9.9 x 104 colonies/mL, 14.3 x 104 colonies / ml and 18.8 x 104 colonies/mL. The pH value is obtained at a temperature of 0  with a storage duration of 0 hours, 24 hours, and 48 hours, namely 7.1, 7.2 and 7.3. The pH value is obtained at a temperature of 5  with a storage period of 0 hours, 24 hours, and 48 hours, namely 7.1, 7.7 and 7.8. The pH value is obtained at a temperature of 27  with a storage period of 0 hours, 24 hours, and 48 hours, namely 7.2, 5.7 and 5.6. Based on the results of the research conducted, it can be concluded that the treatment of storage temperature and storage duration can affect physical characteristics, Total Plate Count (TPC) value and pH value in tilapia which shows the quality of freshness of the fish.